Translaminar screw fixation in the lumbar spine: technique, indications, results - Grob, D. (Springer-Verlag, 2014)
Translaminar screw fixation of the lumbar spine represents a simple and effective technique for short segment fusion in the degenerative spine. Clinical experience with 173 patients who underwent translaminar screw fixation revealed a fusion rate of 94%. The indications for translaminar screw fixation as a primary fixation procedure are: segmental dysfunction, lumbar spinal stenosis with painful degenerative changes, segmental revision surgery after discectomies, and painful disc-related syndromes such as internal disc disruption and lumbar disc herniation with concomitant degenerative changes. As an additional stabilization procedure, translaminar screws can be used to augment anterior fusion or reinforce pedicle systems. Translaminar screw fixation achieves as high fusion rate provided the biomechanical principles of the lumbar spine with an intact anterior column are respected and a meticulous operative technique is employed to enhance bony ingrowth of the graft.